2012
DOI: 10.2534/jjasnaoe.16.131
|View full text |Cite
|
Sign up to set email alerts
|

Residual Hull Girder Strength of Asymmetrically Damaged Ships

Abstract: SummaryThis paper discusses the influence of the rotation of the neutral axis on the residual hull girder strength of asymmetrically damaged ships under longitudinal bending. Progressive collapse analysis of the damaged cross section is performed applying the Smith's method for the biaxial bending problem. An explicit expression of the location of the neutral axis including its rotation is given as a function of biaxial curvatures. The procedures of the progressive collapse analysis of the cross section under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…In this case, the Smith method needs to be updated to include the progressively changing of the neutral axis rotations. Fujikubo et al (2012b) studied the influence of the neutral axis rotations on the damaged hull girders using the Smith's method, where they showed that the neutral axis rotations have a significant impact on the residual strength of asymmetrically damaged hulls which may reach as far as 8%. Joonmo et al (2012) adopted a different approach to deal with the translation and rotation of the neutral axis.…”
Section: Damaged Ship Structuresmentioning
confidence: 99%
“…In this case, the Smith method needs to be updated to include the progressively changing of the neutral axis rotations. Fujikubo et al (2012b) studied the influence of the neutral axis rotations on the damaged hull girders using the Smith's method, where they showed that the neutral axis rotations have a significant impact on the residual strength of asymmetrically damaged hulls which may reach as far as 8%. Joonmo et al (2012) adopted a different approach to deal with the translation and rotation of the neutral axis.…”
Section: Damaged Ship Structuresmentioning
confidence: 99%
“…The ultimate strength analyses were carried out using the Smith method in Fujikubo et al (2012) and limited to vertical bending in the current study. It has proved to be a practical approach with satisfactory engineering accuracy and is therefore commonly accepted for assessment of the ultimate strength due to vertical and horizontal bending moments.…”
Section: Ultimate and Residual Strength Analysesmentioning
confidence: 99%
“…Figures 9 and 10 for intact conditions. Second, the Smith method in Fujikubo et al (2012) shall be applied in the cross-section where most of the structure's elements are removed because of the collision damage. This means that the shape of the damage opening and its location are important.…”
Section:  Damaged Conditionsmentioning
confidence: 99%
“…In the case of an asymmetric stress-strain, the neutral axis does not only translate, but also rotate. Fujikubo et al [13] found that the influence of the rotation of the neutral axis on the accuracy of residual strength may be as large as 8%. In order to account for the rotation, Joonmo et al [14] proposed a force vector equilibrium method where both the force and moment at the cross-section are in equilibrium.…”
Section: Introductionmentioning
confidence: 99%